Nós museológicos: os discursos Queer nas exposições Homo (queer remixed) (2007) e QueerMuseu: cartografias da diferença na arte brasileira (2017) - Nunes, Samarone da Silva (2019)
This reflexive writing is the result of the displacements of the "fieldwork" and the "ethnographic" doing. This one considers with special attention the political and epistemological implications of the differences when they undergo processes of capture. Suggestions for these processes emerge when comparing Queer speeches in the Homo (queer remixed) exhibited at the Museu Antropológico (UFG) in Goiânia, Goiás (2007) and QueerMuseu: cartografias da diferença na arte brasileira, shown at Centro Cultural Santander – Porto Alegre, Rio Grande do Sul (2017), Brazil. Contemporary productions such as "epicenters" of conflicts or as mnemonic triggers are shown, described and accessed, according to the proposal to redesign a seam pierced by several narratives in which one of them is a mediator. The dissertation is divided in three chapters in which I expose the problem of the representation of subalternized deviant groups and I gather the Digital Fund of the exhibition at the Museu Antropológico (UFG), mapping and recomposing memories. For this, retrieve of personal files, memories, virtual sources, internet, files and productions in electronic medium. I propose, therefore, reflection on outsourced conflicts, impacts of the reverberations that the peripheral-center inverse displacements can cause. All this bearing in mind the theoretical filters selected between the queer and not (explicitly) queer for the present work, if not untie, at least begin to characterize the knots and nodes left in the tropus of the expository fact by the attempt to capture the Queer in these places and in the brazilian system of arts.